The preparation and characterization of graphene oxide-multiwalled minocycline coatings on ultrafine-grained titanium implants for enhanced performance studies - Liu, Ying; Niu, Chenyang; Chu, Minghui; Liu, Mingda; Chi, Yanxia (Frontiers in Oral Health, 2025)
As the dental implant restoration technology is constantly applied and developed, implant fracture and related infections have emerged as significant factors threatening the long-term outcome of implants. Hence, this experiment intends to bestow the implant itself with anti-fracture and antibacterial capabilities by utilizing ultrafine-grained titanium, which possesses relatively superior mechanical properties, as the implant material and depositing a graphene oxide-minocycline composite coating on its surface. This is done to prevent implant fracture and the initial attachment of early microorganisms, and to strive to impede the colonization of late microorganisms and the formation of infectious biofilms, thereby achieving long-term stability of the implant. The graphene oxide-minocycline composite coating can be successfully fabricated on the surface of ultrafine-grained titanium via electrochemical deposition and liquid-phase deposition techniques, which can enhance the hydrophilicity of ultrafine-grained titanium and exhibit good coating adhesion. It demonstrates excellent antibacterial properties against Staphylococcus aureus, has no in vitro hemolysis, and shows no obvious cytotoxicity to mouse pre-osteoblasts.